A Constructivist Approach to Design Effective Music-Specific Professional Development Strategies for Kindergarten Educators in China: A Qualitative Study - Zhao, Jie; Kassim, Nor Fauzian; Jaafar , Fauziah Md (Journal of Ecohumanism, 2025)
Music-Specific Professional Development (MSPD) is essential to study the impact of active learning techniques and collaborative approach in Chinese kindergarten music educators. Music education is a critical component of early childhood development, which calls for increased participation in MSPD to foster constructivist approach in redefining the strategies to achieve maximum student related outcomes. A qualitative approach using thematic analysis of data from peer reviewed scholarly articles have been undertaken. Major findings emphasize on implementation of blended learning programs, professional learning communities and integration of ICT and artificial intelligence to enhance increased participation in MSPD programs. Teacher perceive MSPD as an effective tool to improve overall wellbeing and cognitive abilities in children, but are limited by lack of resources and enough training. Future research is required to discover broader implications on music pedagogy.